Novel 3D printing method to reinforce implant‐supported denture fiberglass as material for implant prosthesis: A pilot study - Andrea Nicali; Giulia Pradal; Gianluca Brandolini; Andrea Mantelli; Marinella Levi (Wiley, 2022)
Abstract Objectives Despite a large amount of materials and methods to make an implant‐supported denture, nowadays there is no gold standard. Every solution has pros and cons that guide the clinician and the technician to choose the best solution for a single case. The aim of this study was to evaluate the mechanical characteristics of the fiber‐reinforced composite superstructure made by using a novel three‐dimensional (3D) printing technology able to create a reinforcing structure patient‐specific, more reliable, structurally optimized, and faster than conventional methods. Materials and Methods To evaluate mechanical performances of 3D‐printed fiberglass, mechanical characterization of 3D‐printed material was performed. Before proceeding with the realization of the final prosthesis, five specimens were created on which the tensile test and volumetric fiber content measurement were performed. Then denture reinforcement 3D printing process began. Initially, the robot prints layers of fiber. Finally, the obtained 3D‐printed reinforcement structure was finalized in the lab. Results The prosthesis obtained through this process was lighter than a traditional prosthesis, there was a greater chemical adhesion between resin and 3D‐printed reinforcement structure and a better result was obtained from an esthetic point of view. Conclusions The outcomes we obtained endorse its performance both mechanical and esthetic. The entire process is automatic and does not require human operation thanks to specific software programming.